Identification of regulons modulating the transcriptional response to SARS-CoV-2 infection in humans - Padilla-Gálvez, Mónica; Arteaga-Vazquez, Leo J.; Villaseñor-Altamirano, Ana B.; Balderas-Martínez, Yalbi Itzel; Collado-Torres, Leonardo; De Las Rivas, Javier; Blanco-Melo, Daniel; Medina-Rivera, Alejandra (Frontiers in RNA Research, 2024)
We appreciate your consideration of our manuscript entitled "Identification of regulons modulating the transcriptional response to SARS-CoV-2 infection in human" for publication in the Frontiers in RNA Research. We thank you and the reviewers for your invaluable feedback during the review process. We have addressed the reviewers' comments and incorporated necessary revisions to enhance the clarity of our work.Below, we address each of the reviewer's comments point-by-point and highlight where changes were made in the manuscript's main text. We greatly appreciate the thoughtful reviews; the reviewers' suggestions have greatly improved our work. We expect this manuscript to be of interest to the scientific community. We hope you now find it acceptable for publication.Sincerely,